(untitled) (Research, Society and Development, 2022)
Nursing presents care as a pillar of the profession, which can be developed both in illness and in health, for the promotion or assistance of the assisted person. When viewing health work, we realize that the act of caring for life, in general and for others, is the result of health production. Thus, the object of work of the health professional is the health needs of users, both collectively and individually. This need for care, when influenced by the health professional, has a healthy life as a product, as well as the quality of life of individuals. This work seeks to reflect on the ecosystemic perspective on the organization of nursing work and its relationship with quality of life. This is a reflective, descriptive study. It is essential to carry out and implement the organization of work with a view to well-being, enabling quality of life for health professionals in their given space – environment – ​​territory.